INISIASI MENYUSU DINI (IMD) TERHADAP KELANCARAN ASI PADA IBU MENYUSUI BAYI USIA 0-1 BULAN DI WILAYAH KERJA PUSKESMAS KUTOREJO KABUPATEN MOJOKERTO - Dyah Siwi Hety (MEDICA MAJAPAHIT, 2018)
Early initiation of breastfeeding is the process of letting the baby with own instinct to suckle immediately within the first hour after birth. Early initiation of breastfeeding can help accelerate the expenditure mothers lactic and ensure continuity of expenditure mothers lactic. Because of this reason,Â the writer wants to know relationship between the initiation of early breastfeeding and acceleration of lactic produce in the mothers breastfeeding their babies aged 0-1month in the Work Area of public health centers at Kutorejo Mojokerto. Design of this study is Observational with case-control. The study had been conducted by 14 respondents of mothers breastfeeding their babies aged 0-1 month. The general data observed are age, occupation and education. The particular data are early breastfeeding initiation and acceleration of lactic. The results of study showed that mothers who initiate early breastfeeding smoothly amount 10 respondents (71,4%), and who initiate early breastfeeding unwell amount 2 respondents (14,3%). While, who donâ€™t initiate early breastfeeding smoothly amount one respondent (7,1%), who donâ€™t initiate early breastfeeding unwell amount one respondent (7,1%). The results of test of fisher exact with significant level 0,05, explain the results Ï value > 0,05, so the zero hypothesis (H0) is accepted and (H1) is rejected that means there is not relationship between early breastfeeding initiation with acceleration of lactic. It shows that succesfull early breastfeeding initiation can accelerate lactic production, the other factors that can be influenced the acceleration ofÂ lactic, are the frecuency of lactation, the condition of mothersÂ must relax, the nutrition, giving an extra milk, and breast care. The benefits for the writer, education, institution, respondents, and the place of study are additional knowledge, giving information, improving knowledge, and giving nursing care in the implementation early breastfeeding initiation that can be accelerate the lactic production in the mothers